Modeling of buoyancy-driven thermal convection in immersed granular beds. (January 2021) - Dbouk, Talib; Bahrani, S. Amir
Highlights: Modeling of thermal convection in immersed granular beds induced by local heating. Buoyancy-driven destabilization in immersed granular beds. Critical Rayleigh number and destabilization phenomena in granular beds. Abstract: For the first time, Eulerian three-dimensional transient modeling of thermal convection in immersed granular beds (IGB) has been developed. The modeling accounts for the destabilization of the IGB and the granular boundary upper layer deformation induced by thermal heating element. As observed in the recent experiments, the developed 3D CFD model predicts well the local phenomena: destabilization onset, particles removal or ejection, and the dynamic granular boundary upper layer deformation. The model predicts with good accuracy the two destabilization times t d, onset, and t d, total as function of the IGB initial height h i . Innovatively, a new critical Rayleigh number R a c r * was introduced as function of a locally measured critical temperature Tcr at t = t c r > t d, o n s e t . The critical time tcr corresponds to a critical temperature drop observed inside the IGB near the heating element that was locally measured. The CFD model predicts correctly the thermal phase stability diagram, based on R a c r * versus h i, as observed experimentally.